External Border Gateway Protocol (EBGP) Routing Design in Router Core - Nico Hadipratama; Desmulyati Desmulyati; Andi Taufik (Jurnal Mantik, 2020)
An autonomous system (AS) is the collection of networks having the same set of routing policies. Each AS has administrative control to its own inter-domain routing policy. Computer networks consisting of a bunch of AS's with different routing will not be able to interconnecttion one another. This is causes communication in the network to be inhibited. For that we need a protocol that can connect each different AS. External Border Gateway Protocol (EBGP) is an inter-domain routing protocol ie between different AS that is used to exchange routing information between them. In a typical inter-network (and in the Internet) each autonomous system designs one or more routers that run EBGP software. EBGP routers in each AS are linked to those in one or more other AS. The ability to exchange table routing information between Autonomous System (AS) is one of the advantages of EBGP. EBGP implements routing policies based on a set of attributes accompanying each route used to pick the "shortest" path across multiple AS, along with one or more routing policies. EBGP uses an algorithm which cannot be classified as a pure "Distance Vector", or pure "Link State". It is a path vector routing protocol as it defines a route as a collection of a number of AS that is passes through from source AS to destination AS. This paper discusses the implementation of the EBGP routing protocol in the network that have different AS in order to interconnect. Its application using Graphic Network Simulator (GNS3) software for prototyping and simulating network. So that later can be applied to the actual network.